Detecting spinal pyramidal tract of amyotrophic lateral sclerosis patients with diffusion tensor tractography. (August 2018) - Fukui, Yusuke; Hishikawa, Nozomi; Sato, Kota; Nakano, Yumiko; Morihara, Ryuta; Shang, Jingwei; Takemoto, Mami; Ohta, Yasuyuki; Yamashita, Toru; Abe, Koji
Highlights: We evaluated the cervical fiber tracts reconstructed as DTI tracking images. The FA values of ALS-total and ALS-limb patients were significantly reduced. In ALS patients, rates of disease progression were negatively correlated with FA. The rates of disease progression were also positively correlated with CMCT. Abstract: The objective of this study was to determine alteration of corticospinal tract in patients with amyotrophic lateral sclerosis (ALS) using diffusion tensor tractograhy (DTT) focusing on the cervical spinal cord (C5) and transcranial magnetic stimulation (TMS). We recruited 38 ALS, 6 spinal and bulbar muscular atrophy (SBMA), 7 spastic paraplegia (SP) patients, and 8 age-matched normal controls, and then ALS were divided into two subgroups according to their clinical type: 28 ALS-limb and 10 ALS-bulbar. DTT was performed using the diffusion tensor image (DTI) track module to reconstruct two fiber tracts via C5. The fractional anisotropy (FA) values of ALS-total and ALS-limb patients were significantly reduced compared with normal controls, and SBMA patients. On the other hand, the mean diffusivity (MD) values were not significantly different among normal controls and the three disease groups. The rate of disease progression (ΔFRS-R) of ALS patients was significantly correlated with FA values and central motor conduction time (CMCT). In conclusion, the present study demonstrated a significant reduction of FA values in ALS patients, and the ΔFRS-R of ALS patients showed distinct regressions with FA values and CMCT, suggesting that this DTT analysis could be useful for detecting disease progression of ALS patients.